2022
DOI: 10.3390/pharmaceutics15010094
|View full text |Cite
|
Sign up to set email alerts
|

Indene-Derived Hydrazides Targeting Acetylcholinesterase Enzyme in Alzheimer’s: Design, Synthesis, and Biological Evaluation

Abstract: As acetylcholinesterase (AChE) plays a crucial role in advancing Alzheimer’s disease (AD), its inhibition is a promising approach for treating AD. Sulindac is an NSAID of the aryl alkanoic acid class, consisting of a indene moiety, which showed neuroprotective behavior in recent studies. In this study, newer Indene analogs were synthesized and evaluated for their in vitro AChE inhibition. Additionally, compared with donepezil as the standard drug, these Indene analogs were accessed for their cell line-based to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These plants are traditionally used to get relief from stressful conditions and are previously stated in the literature for the same cause [48–51] . Thus, these diverse ligands from herbal source were considered in the molecular library with intent to recognize the most optimized lead responsible for the generation of antistress effect in humans as well as establishing the likely physiological mechanism involved in the stress relieving effect of that particular active ingredient from these plants [52–54] …”
Section: Methodsmentioning
confidence: 99%
“…These plants are traditionally used to get relief from stressful conditions and are previously stated in the literature for the same cause [48–51] . Thus, these diverse ligands from herbal source were considered in the molecular library with intent to recognize the most optimized lead responsible for the generation of antistress effect in humans as well as establishing the likely physiological mechanism involved in the stress relieving effect of that particular active ingredient from these plants [52–54] …”
Section: Methodsmentioning
confidence: 99%
“…[28][29][30][31][32][33] AutoDock Tools software was used to identify active binding pockets within the macromolecular target and used to prepare the imaginary grid box. [34][35][36][37][38] The grid parameters used in the current study were tabulated in table 1.…”
Section: Molecular Docking Based Screeningmentioning
confidence: 99%
“…Molecular docking based computational screening were performed by using AutoDock 4.2 software of the prepared ligand library against the predicted therapeutic targets for ulcerative colitis [28–33] . AutoDock Tools software was used to identify active binding pockets within the macromolecular target and used to prepare the imaginary grid box [34–38] . The grid parameters used in the current study were tabulated in table 1.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Thus, the library of the indene analogs was prepared and detailed in silico analysis was reported in our previous publication. 10 Further, our next publication reported the in vitro analysis of the indene methylene analogues. 11 The encouraging results in these studies showed indene nucleus attached to the linker, substituent and tailing group are vital for the activity.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Further, our next publication reported the in vitro analysis of the indene methylene analogues. 11 The encouraging results in these studies showed indene nucleus attached to the linker, substituent and tailing group are vital for the activity. Hydroxy substitution at para and ortho positions was found to be most active against AChE.…”
Section: Introductionmentioning
confidence: 99%